MAKNA GERAK TIDI LO TIHU’O GORONTALO - Yahya, Mayawi; Djafar, Nurlia; Pulukadang, Mimy Astuty (Jurnal Bahasa, Sastra, dan Budaya, 2026)
Tidi Lo Tihu’o is a traditional dance from Gorontalo that embodies strong philosophical values related to the life phase of adolescent girls. This dance functions not only as an expression of aesthetic beauty but also as a medium for conveying moral, social, and spiritual messages. This study aims to analyze the movement patterns of Tidi Lo Tihu’o based on the concepts of meaningful movements and pure movements, as well as to reveal the meanings contained within them. The research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results indicate that the movement patterns of Tidi Lo Tihu’o are a combination of meaningful and pure movements representing values of self-control, togetherness, emotional management, and the prayers and hopes of parents for Gorontalo adolescent girls.